2021
DOI: 10.1016/j.psychres.2021.114146
|View full text |Cite
|
Sign up to set email alerts
|

Are the kids really alright? Impact of COVID-19 on mental health in a majority Black American sample of schoolchildren

Abstract: Children from historically disadvantaged groups (racial minorities, lower socioeconomic status [SES]) may be particularly susceptible to mental health consequences during the COVID-19 pandemic. We examined the impact of the pandemic, including mental health symptoms and COVID-19-related fears and behaviors, in a sample of majority Black American (72%) children ( n =64, ages 7–10, 24 female) from an urban area with high infection rates. Children completed a mental health screening form pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…Bhogal et al ( 2021 ) also raise concerns that the COVID-19 pandemic might have differential effects on mental health for children from cultural minorities (see also Sneed et al, 2020 ): Referring on Black American communities in the United States, the authors assumed that the pandemic has specific consequences such as a fear of cultural bias regarding the diagnostic and treatment of COVID-19 or a re-traumatization of already-traumatized humans. Analyzing Austrian adolescents during the COVID-19 pandemic, Pieh et al ( 2022 ) found that the migration background was associated not only with a poorer mental health but also with a lower SWB in children during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Bhogal et al ( 2021 ) also raise concerns that the COVID-19 pandemic might have differential effects on mental health for children from cultural minorities (see also Sneed et al, 2020 ): Referring on Black American communities in the United States, the authors assumed that the pandemic has specific consequences such as a fear of cultural bias regarding the diagnostic and treatment of COVID-19 or a re-traumatization of already-traumatized humans. Analyzing Austrian adolescents during the COVID-19 pandemic, Pieh et al ( 2022 ) found that the migration background was associated not only with a poorer mental health but also with a lower SWB in children during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that socioeconomic factors may affect the level of perceived fear related to COVID-19, including fear of illness and social distancing. 23 In addition to individual socioeconomic status, including lower education levels, being associated with greater fear, findings have revealed that people in more deprived areas may be particularly vulnerable to the psychological distress caused by the pandemic. 5 , 24 In fact, mental health during the COVID-19 crisis was found to be worse in more deprived areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many adults have also experienced increases in acute stress, anxiety, depression, fear, posttraumatic stress disorder, tension, and suicidal ideation during the pandemic (Baba, 2020; Panchal et al, 2021; Vindegaard & Benros, 2020), with concomitant implications for youth, who are both generally more susceptible to mental health issues than adults and significantly impacted by the struggles of their parents, teachers, and caregivers (Deighton et al, 2019). Students may experience anxiety about members of their family or their friends getting sick with COVID-19, family financial insecurity, or no longer having basic needs met in the household (Bhogal et al, 2021; Deighton et al, 2019). Compared to adults, youth seem more likely to experience moderate to severe symptoms of anxiety and depression (Murata et al, 2020).…”
Section: Calloutsmentioning
confidence: 99%
“…Data indicates that the pandemic has disproportionately impacted minoritized, immigrant, and low-SES populations both globally and in the United States (Bhogal et al, 2021; Czeisler et al, 2020; Sneed et al, 2020), exposing existing inequalities related to healthcare services such as testing and medical access, insurance, treatment options, and resources (Marques de Miranda et al, 2020; Penner et al, 2021; Perry et al, 2021). Potential race, class, language, and gender bias in treatment and hospital protocols or decisions is another factor in the equation (Snowden & Graaf, 2021).…”
Section: Calloutsmentioning
confidence: 99%